Chemputer and chemputation—A universal chemical compound synthesis machine - Leroy Cronin; Sebastian Pagel; Abhishek Sharma (Proceedings of the National Academy of Sciences, 2026)
Chemputation treats chemical synthesis as the execution of reaction code on programmable hardware. We show that a Chemputer, equipped with an extensible set of reagents, catalysts, and process conditions, together with a compiler that maps reaction and hardware graphs, is universal. This means it can produce any stable, isolable molecule in finite time and detectable quantity, provided real-time error correction maintains sufficient step fidelity relative to the number of steps in the synthesis. We formalize this into a Chemical Synthesis Turing Machine (CSTM), which defines chemical execution through a unified description of reagents, process variables, and catalysts. The framework introduces the Universal Chemputation Principle and a dynamic error-correction scheme that enables fault-tolerant synthesis. Linking this framework to assembly theory strengthens the definition of a molecule by demanding practical synthesizability and error correction becomes a prerequisite for universality. We demonstrate the abstraction is universal with more than 100 χDL programs executed on modular Chemputers, from single-step reactions to multistep syntheses. In each case, the number of unit operations scales linearly with synthetic depth. These results establish programmable chemical synthesis, chemputation, as a subset of general computation where χDL programs are compiled to hardware, executed with closed-loop control, and yield verifiable molecular outputs. This formalization enables shareable chemical code, interoperable hardware, and a machine-verifiable, executable foundation for a searchable and formally provable map of chemical space.